Non-malignant Uveitis Masquerade Syndromes - Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The Uveitis Masquerade Syndromes (UMS) are a group of ocular diseases that mimic chronic intraocular inflammation. Many non-malignant conditions may result in an appearance mimicking an uveitis. The authors review most common non-malignant conditions which may be considered masquerades such as: retained intraocular foreign body, rhegmatogenous retinal detachment, myopic degeneration, pigment dispersion syndrome, ocular ischemic syndrome, infectious intraocular inflammation, retinitis pigmentosa, multiple sclerosis and drug and post-vaccination reactions.